Same mesozooplankton functional groups, different functions in three Arctic marine ecosystems. (26th September 2022) - Saint‐Béat, Blanche; Darnis, Gérald; Leclerc, Maxime; Babin, Marcel; Maps, Frédéric
Abstract: The trophic relationships interconnecting marine organisms together into a dynamic trophic network drive the structure and the functioning of the entire ecosystem. Since the flow of carbon within trophic networks is controlled by a variety of functional traits related to food acquisition and individual survival, it is crucial to understand how functional diversity relates to marine ecosystems properties such as the resistance and resilience against perturbations. In the Arctic, marine ecosystems are facing stronger and faster environmental changes than anywhere on Earth, leading to profound perturbations in the planktonic assemblages at the base of the trophic networks. While it is known that mesozooplankton plays a crucial role of matter and energy hub within marine Arctic food web, the precise role of the diverse mesozooplankton functional groups in carbon circulation and in marine ecosystems functioning remains poorly known. We coupled a trait‐based approach of mesozooplankton diversity to an ecological network analysis approach to test whether similar mesozooplankton functional groups played similar ecological roles in three Arctic ecosystems during the summer period. We formed nine mesozooplankton functional groups by gathering different species according to their feeding strategies. Then we implemented those into inverse food web models (linear inverse modelling) describing three contrasted Arctic ecosystems. In each ecosystem, we performed sensitivity analysis experiments where each mesozooplankton functional group was removed one at a time. Our results showed that, although the same main functional groups composed the three ecosystems, the few outstanding changes observed in the carbon circulation within the food web were strongly controlled by both the initial whole‐network properties and productivity of the ecosystem. The various roles played by a given mesozooplankton functional group in the ecosystem depend on its impact on carbon flows through the food web it belongs to. As a result, identifying which functional groups could be threatened, and which carbon flows could be altered by climate change is critical information to predict future ecosystems functioning. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.